Newly recorded leafhoppers of the subfamily Cicadellinae (Hemiptera: Cicadellidae) with description of a new species from Pakistan - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
Pakistani species of the leafhopper subfamily Cicadellinae are reviewed. One new species, Atkinsoniella fistular sp. nov., is described and illustrated, and three species are newly recorded from Pakistan and illustrated: Atkinsoniella opponens Walker, 1851 n. rec., Atkinsoniella thalia Distant, 1918 n. rec. and Kolla insignis Distant, 1908 n. rec.. A key is given to distinguish all the genera (males) in this subfamily from Pakistan.